Bilingual performance and surtitles: translating linguistic and cultural duality in Canada - Ladouceur, Louise (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2014)
In Canada, theatre artists living in a linguistic minority context, such as Francophones in Western Canada and Anglophones in Quebec, are bilingual out of necessity. They have recently explored their bilingualism in playwriting and in performing plays that display various degrees of heterolingualism. This article focuses on the emergence of a bilingual theatre in Canada and the challenges it poses for translation. Surtitles are an asset for these heterolingual plays, allowing them to reach a wider audience without erasing the linguistic and cultural specificity of the original production. The use of surtitles has led to experiments in which translation exceeds its primary function and takes on a creative role within the performance. This opens the way to the exploration of new theatrical aesthetics that showcase the linguistic duality at the heart of the Canadian reality.